(untitled) (American Journal of Interdisciplinary Research and Development, 2025)
This article discusses the scientific research conducted by pedagogical scholars from both Eastern and Western backgrounds regarding ecological education, which is currently a pressing issue. The analysis reflects each scholar’s perspective along with the national values inherent to their respective cultures. Additionally, it highlights the commonalities and differences in the approaches of educators from these two regions.